Design of a 24 GHz frequency divider‐by‐10 in 45 nm‐silicon‐on‐insulator as an active reflector tag. Issue 23 (1st November 2017) - El Agroudy, N.; El‐Shennawy, M.; Joram, N.; Ellinger, F.
Abstract : The design of a 24 GHz frequency divider‐by‐10 for accurate indoor localisation systems is presented. It is proposed to use frequency dividers as active reflector tags in a frequency‐modulated continuous wave indoor localisation system in order to reduce interferences caused by direct reflections of the interrogating signal. Since frequency dividers are subharmonic generators, this allows achieving conversion gain in the reflected signal. The frequency divider is fabricated using GLOBAL FOUNDRIES 45 nm‐silicon‐on‐insulator technology. It consumes only 5.7 mW from a 1 V supply. It has a wide locking range of 33% and an efficiency of 3.58 GHz/mW. To the best of authors' knowledge, the use of frequency dividers as active reflectors was not studied before.